2000
DOI: 10.1021/jp992650z
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Amylose in Aqueous Solution:  Small-Angle X-ray Scattering Measurements and Simulations

Abstract: Small-angle X-ray scattering profiles for an amylose fragment (maltoheptaose) in aqueous solution were observed and compared with the theoretical profiles calculated for an ensemble of chain conformations generated by molecular dynamics simulations and Monte Carlo simulations. The Monte Carlo results based on the disaccharide conformation energy map obtained without explicitly considering surrounding water molecules were in satisfactory agreement with the experimental results, provided that the effective diele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 79 publications
8
60
0
Order By: Relevance
“…It should be noted that the h values in the two solvents can be smaller by about 10% if the polydispersity correction is made for hS 2 i z with M z =M w $ 1:1. Conformational energy maps for both amylose 44,45 and amylose tris(3,5-dimethylphenylcarbamate) 46 have a shallow minimum which allows the left handed helices with various h values. This indicates that h of the amylosic chain may be influenced by a small perturbation, i.e., intramolecular hydrogen bonding, intermolecular hydrogen bonding with solvent molecules, and packing of substituents and solvent molecules, and thus must be susceptible to such effects.…”
Section: Chain Stiffness and Local Conformationmentioning
confidence: 99%
“…It should be noted that the h values in the two solvents can be smaller by about 10% if the polydispersity correction is made for hS 2 i z with M z =M w $ 1:1. Conformational energy maps for both amylose 44,45 and amylose tris(3,5-dimethylphenylcarbamate) 46 have a shallow minimum which allows the left handed helices with various h values. This indicates that h of the amylosic chain may be influenced by a small perturbation, i.e., intramolecular hydrogen bonding, intermolecular hydrogen bonding with solvent molecules, and packing of substituents and solvent molecules, and thus must be susceptible to such effects.…”
Section: Chain Stiffness and Local Conformationmentioning
confidence: 99%
“…In addition, it has been reported that the nucleation rate of sugars, which has to precede crystal growth, is generally very low, so sugars often form supersaturated solutions of syrup-like liquid (36,37). However, several LR-CD structures have been deduced from molecular dynamics simulations and small angle X-ray scattering analysis (38)(39)(40)(41). Recently, a conformation study on LR-CD was reported based on a conformational search with molecular dynamics simulations and principal component analysis (42).…”
Section: B Physicochemical Properties and Molecular Structures Of Lr-cdmentioning
confidence: 99%
“…Several studies used molecular dynamics (MD) simulations (with lengths of 100-400 ps) to examine the macroring conformations of LR-CDs containing 10, 14, 18, 21, 24 and 48 glucose units either in vacuum or in water solution. 37,38,39,40 The circularized three-turn single helical structure proposed for CD21 from small-angle X-ray scattering was shown, with rather short MD simulations (100 ps), to persist in water at 300 K. 34 Recently we reported results from study on CDs with a degree of polymerization of 26,30,35,40,55,70, 85 and 100, using much longer molecular dynamics simulations (5.0 ns for all except for the one of 26 for which the MD was of 10.0 ns). 41,42 Although the results were later published, 43 53 Both, the monitoring of the structural variations during the simulations, as well as the analyses of energy balances were indicative for high flexibility of the macrorings.…”
Section: Introductionmentioning
confidence: 99%